Timely delivery of cardiac mmRNAs in microfluidics enhances cardiogenic programming of human pluripotent stem cells - Contato, Anna; Gagliano, Onelia; Magnussen, Michael; Giomo, Monica; Elvassore, Nicola (Frontiers in Bioengineering and Biotechnology, 2022)
In the last two decades lab-on-chip models, and specifically, heart-on-chip have been developed as promising technologies for recapitulating physiological environments suitable for studies of drug and environmental effects on either human physiological or patho-physiological conditions. Most human heart-on-chip systems are based on integration and adaptation of terminally differentiated cells within microfluidic context. This process requires prolonged procedures, multiple steps, and is associated with an intrinsic variability of cardiac differentiation. In this view, we developed a method for cardiac differentiation-on-a-chip based on combining the stage-specific regulation of Wnt/β-catenin signaling with the forced expression of transcription factors (TFs) that timely recapitulate hallmarks of the cardiac development. We performed the overall cardiac differentiation from human pluripotent stem cells (hPSCs) to cardiomyocytes (CMs) within a microfluidic environment. Sequential forced expression of cardiac TFs was achieved by a sequential mmRNAs delivery of first MESP1, GATA4 followed by GATA4, NKX2.5, MEF2C, TBX3 and TBX5. We showed that this optimized protocol led to a robust and reproducible approach to obtain a cost-effective hiPSC-derived heart-on-chip. The results showed higher distribution of cTNT positive CMs along the channel and a higher expression of functional cardiac markers (cTNT and MYH7). The combination of stage-specific regulation of Wnt/β-catenin signaling with mmRNAs encoding cardiac transcription factors will be suitable to obtain heart-on-chip model in a cost-effective manner, enabling to perform combinatorial, multiparametric, parallelized and high-throughput experiments on functional cardiomyocytes.